Analisis Makna konotatif dan Budaya Jepang: “Iblis” dalam Kanji Ber-Bushu Oni - Ngaziz, Malik; Mulyadi, Budi (KIRYOKU, 2025)
This study examines four kanji characters containing the bushu oni (鬼) that do not lexically mean "demon," yet carry connotative meanings associated with demonic traits. The research aims to reveal these connotations through semantic and semiotic approaches within the context of Japanese culture. A descriptive qualitative method was employed, based on literature review. The structural analysis of the kanji was conducted using the Rikusho theory to determine character formation types, while Roland Barthes’ semiotic theory was applied to interpret the cultural symbolism embedded in each character. The results indicate that the four analyzed kanji Tamashii, Minikui, Sakigake, Mi (魂, 醜, 魁, and 魅) share associative meanings with the traits of oni in Japanese mythology such as supernatural power, seductiveness, or grotesque appearance despite lacking direct lexical links to “demon.” These findings demonstrate that the bushu oni radical can represent complex cultural values, not always negative, depending on the context. This study contributes to kanji semantics by uncovering the connotative meanings of the bushu 鬼 within Japanese cultural frameworks.